9000070702

Podoblasť: 
Časť: 
Project ID: 
9000070702
Accepted: 
1
Určte prvú deriváciu funkcie \(f\colon y = (x^{2} - 3x + 2)^{\frac{1} {2} }\).
\(f^{\prime}(x) = \frac{2x-3} {2\sqrt{x^{2 } -3x+2}};\ x\in \mathbb{R}\setminus \left \langle 1;2\right \rangle \)
\(f^{\prime}(x) = \frac{2x-3} {2\sqrt{x^{2 } -3x+2}};\ x\in \mathbb{R}\setminus \left (1;2\right )\)
\(f^{\prime}(x) = (4x - 6)\sqrt{x^{2 } - 3x + 2};\ x\in \mathbb{R}\setminus \left \langle 1;2\right \rangle \)
\(f^{\prime}(x) = (4x - 6)\sqrt{x^{2 } - 3x + 2};\ x\in \mathbb{R}\setminus \left (1;2\right )\)